Phototriggers for light-controlled activation and release applications - Costa, Susana P. G. (2017)
Comunicação oral convidada IOC4 no XXV Encontro Nacional de Sociedade Portuguesa de Química, Lisboa, Portugal, 16-19 de Julho de 2017.